Modeling the Causal Relationship between Self-Directed Learning Skills, Learning Styles and Academic Achievement of the Community College Students at King Saud University - Alotaibi, Khaled (Jordan Journal of Educational Sciences, 2015)
This study aimed at identifying the direct and indirect effects of self-directed learning skills, learning styles and academic achievement through modeling the causal relationship between them. To achieve this aim, the researcher applied Williamson’s self-rating scale of self-directed learning (2007) and Entwistle and Tait’s (1994) adjusted learning style scale to a random sample of (140) students of the Community College at King Saud University. The results indicated that the students had a moderate level of self-directed learning skills, and that superficial and strategic learning styles were the most common learning methods. In addition, the results showed that the direct effect of learning styles, except the strategic style, on academic achievement differed from the indirect effect. However, the indirect effect was much greater than the direct effect after the mediation of self-directed learning skills. This means that these skills play a mediating role in the relationship between learning styles and academic achievement